Recent advances in the application of water-stable metal-organic frameworks: Adsorption and photocatalytic reduction of heavy metal in water - Li, Zhongwu; Wang, Lei; Qin, Lei; Lai, Cui; Wang, Zhihong; Zhou, Mi; Xiao, Linhui; Liu, Shiyu; Zhang, Mingming (Chemosphere (Oxford), 2021)
Heavy metals pollution in water is a global environmental issue, which has threatened the human health and environment. Thus, it is important to remove them under practical water environment. In recent years, metal-organic frameworks (MOFs) with water-stable properties have attracted wide interest with regard to the capture of hazardous heavy metal ions in water. In this review, the synthesis strategy and postsynthesis modification preparation methods are first summarized for water-stable MOFs (WMOFs), and then the recent advances on the adsorption and photocatalytic reduction of heavy metal ions in water by WMOFs are reviewed. In contrast to the conventional adsorption materials, WMOFs not only have excellent adsorption properties, but also lead to photocatalytic reduction of heavy metal ions. WMOFs have coupling and synergistic effects on the adsorption and photocatalysis of heavy metal ions in water, which make it more effective in treating single pollutants or different pollutants. In addition, by introducing appropriate functional groups into MOFs or synthesizing MOF-based composites, the stability and ability to remove heavy metal ions of MOFs can be effectively enhanced. Although WMOFs and WMOF-based composites have made great progress in removing heavy metal ions from water, they still face many problems and challenges, and their application potential needs to be further improved in future research. Finally, this review aims at promoting the development and practical application of heavy metal ions removal in water by WMOFs. •Heavy metal ion pollution of water bodies has led to serious harm.•The removal of heavy metal ions in water by WMOFs is summarized.•Adsorption and photocatalytic reduction of heavy metal ions by WMOFs are reviewed.•Synthesis strategies and postsynthesis modification of WMOFs are summarized.